Interpolasi Lagrange dalam Pembuatan Interface Prediksi Jumlah Penduduk NTT Berbasis Python - Muhammad Naufal Daru Ciptoning; Nabilah Nesya Adiarni Azzahra; Ermelya Helmi Anggraeni; Arum Nanda Putri Aprilia; Rahmawati Erma Standsyah; Dian Savitri (Mathematics Department, Faculty of Sciences and Technology Unisda Lamongan, 2026)
This study aims to implement the Lagrange interpolation method in a Python-based Graphical User Interface (GUI) application to predict the population of Nusa Tenggara Timur (NTT) Province. The development of this system was necessary because of the limited number of practical computer tools capable of estimating the population between times for official censuses. The Lagrange interpolation method is applied to construct a polynomial curve based on historical population census data, which is then integrated into a Python-based interactive system. The application interface is designed to allow users to input the prediction year and automatically obtain estimation results along with graphical visualization. The testing results indicate that the system performs interpolation computations accurately, producing results consistent with manual mathematical calculations. Furthermore, the graphical visualization demonstrates that the population estimation curve follows the trend of historical data. Therefore, the developed system simplifies numerical computation while providing a practical digital tool to support regional demographic analysis and planning.